2018
DOI: 10.1210/en.2018-00048
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Maturation of Human Embryonic Stem Cell–Derived β Cells in Mice

Abstract: Pancreatic progenitors derived from human embryonic stem cells (hESCs) are now in clinical trials for insulin replacement in patients with type 1 diabetes. Animal studies indicate that pancreatic progenitor cells can mature into a mixed population of endocrine cells, including glucose-responsive β cells several months after implantion. However, it remains unclear how conditions in the recipient may influence the maturation and ultimately the function of these hESC-derived cells. Here, we investigated the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…The cellular and molecular basis of the process driving this in vivo terminal differentiation is not yet completely understood 11 . Different potential scenarios include the involvement of circulating factors [12][13][14][15] , nervous system association [16][17][18] and the presence of a 3D niche 19,20 , amongst others. Discriminating the exact contribution of each of these potential scenarios on the transplanted hPSC-derived cells is difficult due to the inherent complexity of the organism environment.…”
Section: Introductionmentioning
confidence: 99%
“…The cellular and molecular basis of the process driving this in vivo terminal differentiation is not yet completely understood 11 . Different potential scenarios include the involvement of circulating factors [12][13][14][15] , nervous system association [16][17][18] and the presence of a 3D niche 19,20 , amongst others. Discriminating the exact contribution of each of these potential scenarios on the transplanted hPSC-derived cells is difficult due to the inherent complexity of the organism environment.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it is, however, expected that a very brief in vivo exposure, such as the one used in this study, will be insufficient to promote any meaningful/detectable improvement in the functionality of the transplanted cells. Indeed, previous studies reported improved functionality and glucose stimulated insulin secretion in similar setups only after about 60 days post xenotransplantation (Rezania et al, 2014;Saber et al, 2018), thus involving longer exposure times.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, xeno-transplantation into living hosts, such as mice, has been shown to significantly increase the yield and functionality of the differentiating hPS-derived cells (Kroon et al, 2008;Rezania et al, 2012Rezania et al, , 2014Pagliuca et al, 2014). Indeed, after extensive periods of time (2-6 months), the xenotransplantation of circa two million in vitro differentiated cells was able to normalize the glycemia in diabetic mice (Pagliuca et al, 2014;Rezania et al, 2014;Agulnick et al, 2015;Vegas et al, 2016;Bochenek et al, 2018;Saber et al, 2018). Although these experiments highlighted the importance of the in vivo environment and its systemic factors in promoting islet cell fate, the signals governing this process are largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that a more committed population may provide faster glycemic control in clinical settings. Well-designed studies have also described the in vivo maturation of hESC-derived PPs in various settings: 1) with and without encapsulation (9,42,64), 2) in male vs. female hosts (67), 3) in rats vs. mice (8), 4) in high-fat diet (10), 5) during pregnancy (67), and 6) in a model of hypothyroidism (11). These studies suggest that host environment, sex differences, and disease conditions may play crucial roles in PP maturation in vivo.…”
Section: Functionalitymentioning
confidence: 99%